Mitigation of salt stress on low temperature in bermudagrass: resistance and forage quality - Zhou, Xiuwen; Yin, Yanling; Wang, Guangyang; Amombo, Erick; Li, Xiaoning; Xue, Ying; Fu, Jinmin (Frontiers in Plant Science, 2022)
In today's environment, plants are exposed to an increasing number of abiotic stress combinations. Previous research had focused on a single stress, but this study coupled low temperature and salt stress. The response mechanism of bermudagrass to low temperature and salt treatment was investigated in this study. The results showed that low temperature (LT) treatment decreased the relative growth rate, chlorophyll fluorescence transient curve, biomass, and crude fat content of bermudagrass, whereas low temperature + salt (LT+S) treatment greatly undermined these declines. Furthermore, at 6 h and 17 d, the expression levels of glyoxalase I (GLYI), Cu-Zn/superoxide dismutase (Cu-Zn/SOD), peroxidase 2 (POD2), and oxidative enzyme 1(CAT1) in roots were considerably higher in the low temperature + salt treatment than in the low temperature treatment. Low temperature stress is more detrimental to bermudagrass, but mild salt addition can mitigate the damage by enhancing photosynthesis and improving the expression of antioxidant system genes (Cu-Zn /SOD, POD2 and CAT1) and glyoxalase system GLYI gene in roots. By understanding the probable response interaction mechanism, our work can provide useful reference for the growth of fodder in cold places.